Performance assessment of a vertical axis turbine in a marine current flume tank and CFD modelling. (December 2015) - Rolland, S.A.; Thatcher, M.; Ellis, R.; Gaurier, B.; Croft, T.N.; Cross, M.
Highlights: Identification of the energy conversion mechanisms in a vertical axis turbine. Validation of a CFD model with experimental performance data and PIV. Turbine performance increases with Reynolds number due to changes in flow regime. Abstract: As advances in numerical modelling techniques support the increased confidence in predictions from computer simulations, the need remains to have experimental verification built into the design process. This paper outlines the experimental investigation carried out on a shielded vertical axis turbine in a marine environment. The experiments consist of performance measurements and the use of particle image velocimetry on a small scale device in a marine current flume. The results demonstrate that the performance of the device can be modelled numerically; in particular, the results show that the numerical model used can correctly predict the increase in performance with Reynolds number.